Influence of Foliar Sprays of 2,4-D, Urea, Zinc Sulphate, Bavistin and their Combinations on Growth, Yield and Leaf Chlorophyll Content of Kinnow Mandarin - Saini, Poonam; Rana, G. S.; Anuradha; Pooja (International Journal of Bio-resource and Stress Management, 2025)
The experiment was conducted during March, 2019-November, 2020 at the experimental orchard, Department of Horticulture, CCS Haryana Agricultural University, Hisar, to find out the best concentration of foliar application of growth regulators, nutrients and fungicides in improvement of growth and chlorophyll content of leaves. Total eighteen treatments, i.e., 2,4-D 10 ppm, 2,4-D 15 ppm, GA3 15 ppm, GA3 20 ppm, Urea 1%, Urea 1.5%, Zinc Sulphate 0.5%, Zinc Sulphate 0.75%, Bavistin 1000 ppm and their combinations with three replications on 9-year-old Kinnow plants were taken. The growth parameters i.e., plant spread (4.90 m (EW) and 4.68 m (NS); 5.02 m (EW) and 4.84 m (NS) during 2019–20 and 2020–21, respectively), trunk diameter (28.31 cm and 28.74 cm during 2019–20 and 2020–21, respectively), leaf area (30.54 cm2 and 31.58 cm2 during 2019–20 and 2020–21, respectively) and leaf chlorophyll content (2.01mg g-1 of fresh weight and 2.19 mg g-1 of fresh weight during 2019–20 and 2020–21, respectively) and yield (75.46 kg/plant and 78.92 kg/plant during 2019–20 and 2020–21, respectively) were found maximum with foliar application of 2,4-D 15 ppm+Urea 1.5%+Zinc Sulphate 0.75%+Bavistin 1000 ppm. Plant height (4.87 m and 4.99 m during 2019–20 and 2020–21, respectively) was effectively improved by foliar application of GA3 20 ppm+Urea 1.5%+Zinc Sulphate 0.75%+Bavistin 1000 ppm.